Development of LKPD Natural Sciences Based on Literacy and Numeration Assisted by Augmented Reality Media in Islamic Elementary School - Ida Fiteriani; Ayu Reza Ningrum; Zalik Nuryana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The study aims to produce a Science Student Worksheet (LKPD) based on literacy and numeracy assisted by augmented reality media at the State Islamic Elementary School (MIN) of Bandar Lampung. This development research uses the ADDIE model which consists of five steps, namely: analysis, design, development, implementation, and evaluation. The subjects in this research are V class of MIN Bandar Lampung students. Data collection techniques apply to a questionnaire. Data analysis techniques in this study used qualitative and quantitative analysis techniques. Qualitative data is obtained from input from experts/validators when validating material, media, and language. Meanwhile, quantitative data are obtained from a two-sample comparative test t-test and N gain test. Based on the validation results, it has fulfilled several predetermined indicators, namely: a) Content Eligibility with an average value of 3.33; b) Oriented towards the development of LKPD with Literacy content with an average value of 3.28; and, c) Oriented to the Development of LKPD with a numerical content of an average value of 3.31. The linguist validator has also met several language indicators which have been set at 3.40 with a valid assessment category. On the practical aspect, an average value of 3.38 is obtained with the valid category. And the average value of attractiveness based on student responses is 3.27 which is included in the attractive category. This LKPD is interesting because an explanation of the experimental activities and the use of AR media is complemented by how to use it so that work mechanisms/procedures are also presented with props.